2004
DOI: 10.1002/aoc.645
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular structures and properties models of macrocyclic polymer complexes

Abstract: Two novel supramolecular complexes of types [Ru(L)(H 2 L)Cl·OH 2 ] and [Ru(HL n )Cl 3 ] (where H2L is a potential tetradentate ligand derived from hydrazine hydrate and diethyl malonate, and HL n is a potential bidentate ligand derived from coupling of allyl azo-β-diketone) have been synthesized and characterized by elemental analysis, conductance and magnetic measurements, followed by 1 H NMR, to determine the effect of substituents on the intramolecular hydrogen bond. The electronic properties and models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Steric factors prevent the coordination of all the donors to a single metal ion. This mode of complexation is confirmed by the appearance of new bands due to ν(C=N) and ν(C=O) [12,13,20] with respect to other bands due to ν(C=O) and ν(C=S). The non-ligand bands appearing in the 480-325 and 365-330 cm −1 regions may tentatively be assigned to ν(M-O) and ν(M-S) vibrations, respectively [21].…”
Section: Uranyl(ii) Polymer Complexmentioning
confidence: 56%
See 3 more Smart Citations
“…Steric factors prevent the coordination of all the donors to a single metal ion. This mode of complexation is confirmed by the appearance of new bands due to ν(C=N) and ν(C=O) [12,13,20] with respect to other bands due to ν(C=O) and ν(C=S). The non-ligand bands appearing in the 480-325 and 365-330 cm −1 regions may tentatively be assigned to ν(M-O) and ν(M-S) vibrations, respectively [21].…”
Section: Uranyl(ii) Polymer Complexmentioning
confidence: 56%
“…The ground term for Ru(III) (t 5 2g configuration) is 2 T 2g and the first excited levels in order of increasing energy are 4 T 1g and 2 A 2g , which arise from t 4 2g e 1 g configurations. In most of the Ru(III) complexes the electronic spectra show only charge-transfer bands [20]. It has been observed that charge-transfer bands of the type L xy → t 2g are prominent in the low-energy region, which obscures the weaker d-d transitions.…”
Section: Electronic Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, in the UO 2 2+ case, the uranyl atom should be a six-coordinate octahedron with the oxygen atom in the apical position. 8 Bis(allyl propenyl-2-(4-derivative phenylazo)butan-3-one uranyl has a low solubility in water and in common organic solvents. Therefore, in order to improve solubility, we have synthesized the azoallyl acetoacetate ( Fig.…”
Section: Uo 2 (Chmentioning
confidence: 99%